2018
DOI: 10.1088/2053-1591/aae5b5
|View full text |Cite
|
Sign up to set email alerts
|

Nuanced superconductivity in endohedral gallide Mo8Ga41

Abstract: We report on synthesis and characterization of gallide cluster based Mo 8 Ga 41 superconductor. Transport and magnetization measurements confirm the superconducting transition temperature to be 9.8 K. The upper critical field (H c2 ), lower critical field (H c1 ), Ginzburg-Landau coherence length (ξ GL ) and penetration depth(λ) are estimated to be 11.8T, 150G, 5.2nm, 148nm respectively. The electronic band structure, density of states and phonon dispersion curve calculations are obtained by using Density Func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
3
10
0
Order By: Relevance
“…Interestingly, band structure of Mo 8 Ga 41 features narrow band dispersion whereas the density of states at the Fermi level is dominated by Mo 4d and Ga4p orbital hybridization. 12 The 3D character of dHvA oscillations is consistent with first principle calculations 13 where four different bands cross the Fermi level. Based on the effective masses obtained in our experiment, it is reasonable to α and β frequencies with electron pocket near the Brillouen zone corner and large anisotropic part of the Fermi surface, respectively whereas other frequencies probably arise due to band associated with two hole pockets near the Γ point that exhibit weak coupling with phonons and where superconducting gap is smaller.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Interestingly, band structure of Mo 8 Ga 41 features narrow band dispersion whereas the density of states at the Fermi level is dominated by Mo 4d and Ga4p orbital hybridization. 12 The 3D character of dHvA oscillations is consistent with first principle calculations 13 where four different bands cross the Fermi level. Based on the effective masses obtained in our experiment, it is reasonable to α and β frequencies with electron pocket near the Brillouen zone corner and large anisotropic part of the Fermi surface, respectively whereas other frequencies probably arise due to band associated with two hole pockets near the Γ point that exhibit weak coupling with phonons and where superconducting gap is smaller.…”
supporting
confidence: 80%
“…Its superconducting T c = 9.7 K and upper critical field µ 0 H c2 = 8.36 T. 7 It has been pointed out that, like MgB 2 , Mo 8 Ga 41 is also on the verge of a structural instability, 8,9 exhibits strong-coupling two-gap BCS superconductivity and good flux pinning potential. [10][11][12][13][14][15] In light of the relatively high critical temperature and upper critical field, further studies of this material are highly desirable.…”
mentioning
confidence: 99%
“…Recently, it was suggested that Mo 8 Ga 41 features two-gap superconductivity [10][11][12] that vanishes upon the V for Mo substitution [10]. The material is a member of endohedral gallium cluster compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In the subsequent study by means of muon spin rotation/relaxation spectroscopy, it was suggested [10] that two superconducting energy gaps exist in Mo 8 Ga 41 . Later on, the reports on possible existence of two energy gaps in Mo 8 Ga 41 followed from the critical current [11] and STS measurements [12].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the only known T m Ga n superconductors are low-temperature superconductors, making them potential materials for producing high magnetic fields at low temperatures. This can be observed in the superconductors Mo 8 Ga 41 and Mo 6 Ga 31 -as the electron counts decrease, the T c increases and the clusters form vertex-sharing interactions rather than edge-sharing [9]. MnGa 4.96 is another Ga-rich cluster which crystallizes into a tetragonal unit cell with capped face sharing Mn@Ga 8 clusters and correspondingly exhibits no superconductivity [10].…”
Section: Introductionmentioning
confidence: 99%